The functional voxel algorithm for iterative composition of complex contours - A. A. Sycheva; A. M. Plaksin (Омский научный вестник, 2023)
The analytical representation most accurately describes the geometry of the simulated objects. However, its application is associated with a number of difficulties. In particular, R-functional modeling imposes high requirements to the qualification of the researcher and may require considerable time for modeling due to recursive nesting of calculations. The application of features of functional-voxel models to simplify R-functional modeling of complex contours is considered. The Function of Local Zeroing is proposed as the main tool for iterative modeling of complex contours, including parametric curves. The method of determining the negative area of FLOZ-constructed contour models for further construction of predicate complex functions by means of R-functional operations is described.